Editing the Central Nervous System Through CRISPR/Cas9 Systems - Cota-Coronado, Agustin; Díaz-Martínez, Néstor Fabián; Padilla-Camberos, Eduardo; Díaz-Martínez, N. Emmanuel (Frontiers in Molecular Neuroscience, 2019)
The translational gap to treatments based on gene therapy has been reduced in recent years because of improvements in gene editing tools, such as the CRISPR/Cas9 system and its variations. This has allowed the development of more precise therapies for neurodegenerative diseases, where access is privileged. As a result, engineering of complexes that can access the central nervous system (CNS) with the least potential inconvenience is fundamental. In this review article, we describe current alternatives to generate systems based on CRISPR/Cas9 that can cross the blood–brain barrier (BBB) and may be used further clinically to improve treatment for neurodegeneration in Parkinson’s and Alzheimer’s disease (AD).